Islamic State of Afghanistan : Rebuilding a Macroeconomic Framework for Reconstruction and Growth. (IMF Staff Country Reports; Country Report, 2003)
In this study, economic developments and achievements, the role of the IMF, strong economic recovery, the formulation and implementation of the government's budgetary policy, and the progress made in rebuilding fiscal institutions are first discussed in detail. An overview of the challenges and issues of the authorities faced in the area of monetary and exchange rate policy is also provided. The authorities decided that the primary objective of monetary policy should be to achieve and maintain price stability and thus to restore confidence in the national currency.